Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Pemoderasi: Studi Empiris 2021–2024: Moderasi Profitabilitas pada Hubungan CSR dan Nilai Perusahaan - Pratama, Ine Hanisa; Siti Samsiah; Evi Marlina (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The COVID-19 pandemic has had a profound impact on the global economy, including Indonesia's industrial sector. A number of industrial firms have seen a reduction in their firm value, as reflected by declining stock prices during and after the crisis. One key factor behind this downturn is the suboptimal execution of Corporate Social Responsibility (CSR) initiatives. Companies that fall short in addressing environmental and social responsibilities often face diminished investor confidence, which can adversely affect profitability and firm value. This research investigates the impact of CSR on firm value and explores how profitability moderates this relationship. The study utilizes secondary data derived from annual financial statements of industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2024. Through purposive sampling, 23 companies were selected, yielding 92 firm-year data points. Multiple linear regression analysis is employed as the analytical technique. The findings reveal that CSR disclosure alone does not have a statistically significant effect on firm value. Nevertheless, profitability plays a moderating role, enhancing the positive relationship between CSR disclosure and firm value. This indicates that companies with stronger profitability are better positioned to leverage their CSR efforts to gain investor confidence and boost firm value.